2020
DOI: 10.1063/1.5139266
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field tunable superconducting transition in Nb/Co/Py/Nb exchange spring multilayers

Abstract: Over the last decade, it has been shown that magnetic non-collinearity at an s-wave superconductor/ferromagnet interface is a key ingredient for spin-singlet to spin-triplet pair conversion. This has been verified in several synthetic non-collinear magnetic structures. A magnetically soft and hard ferromagnetic layer combination in a bilayer structure can function as a field tunable non-collinear magnetic structure, which may offer magnetic field tunability of singlet-to-triplet pair conversion. From magnetiza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the following sections we review two relevant aspects of spin-triplet correlations in S/F hybrid structures, based on our previous experiments [25,26]. In the first part we discuss the use of natural ferromagnetic domain walls to achieve spin-singlet to spin-triplet Cooper pair conversion in a planar nano-SQUID structure [25].…”
Section: Experiments On Spin Triplet Correlations In Hybrid S/f Struc...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the following sections we review two relevant aspects of spin-triplet correlations in S/F hybrid structures, based on our previous experiments [25,26]. In the first part we discuss the use of natural ferromagnetic domain walls to achieve spin-singlet to spin-triplet Cooper pair conversion in a planar nano-SQUID structure [25].…”
Section: Experiments On Spin Triplet Correlations In Hybrid S/f Struc...mentioning
confidence: 99%
“…In the first part we discuss the use of natural ferromagnetic domain walls to achieve spin-singlet to spin-triplet Cooper pair conversion in a planar nano-SQUID structure [25]. In the second part we discuss the use of diamagnetic screening currents to probe spintriplet correlations in superconductor/exchange spring multilayer structures [26].…”
Section: Experiments On Spin Triplet Correlations In Hybrid S/f Struc...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in superconducting spintronics, it is essential to generate spin-triplet Cooper pairs on demand [29]. It was reported that in a graphene ferromagnet (F)/SC/F nanostructure [30], the induced equal spin triplet correlations in the SC can be controlled by tuning either the magnetization directions or by manipulating the Fermi level of the F layer.…”
mentioning
confidence: 99%